Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1017/jog.2020.22
|View full text |Cite
|
Sign up to set email alerts
|

Explaining mass balance and retreat dichotomies at Taku and Lemon Creek Glaciers, Alaska

Abstract: We reanalyzed mass balance records at Taku and Lemon Creek Glaciers to better understand the relative roles of hypsometry, local climate and dynamics as mass balance drivers. Over the 1946–2018 period, the cumulative mass balances diverged. Tidewater Taku Glacier advanced and gained mass at an average rate of +0.25 ± 0.28 m w.e. a–1, contrasting with retreat and mass loss of −0.60 ± 0.15 m w.e. a−1 at land-terminating Lemon Creek Glacier. The uniform influence of regional climate is demonstrated by strong corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 77 publications
3
30
0
Order By: Relevance
“…At SCG and LCG, site consistency was not emphasized over much of the record; rather, measurements occurred in general regions (typically, 5–10 sites). JIRP assembled the majority of the LCG record, which is characterized by a single late-summer, accumulation dominated set of annual observations (Pelto and others, 2013; McNeil, 2016). Data from LCG and SCG required additional efforts to prepare input for standard processing (Supplementary Material).…”
Section: Datamentioning
confidence: 99%
“…At SCG and LCG, site consistency was not emphasized over much of the record; rather, measurements occurred in general regions (typically, 5–10 sites). JIRP assembled the majority of the LCG record, which is characterized by a single late-summer, accumulation dominated set of annual observations (Pelto and others, 2013; McNeil, 2016). Data from LCG and SCG required additional efforts to prepare input for standard processing (Supplementary Material).…”
Section: Datamentioning
confidence: 99%
“…Taku Glacier is currently advancing over fjord sediment deposits (Post and Motyka, 1995; McNeil, 2016) and offers an opportunity to study sediments under a tidewater glacier terminus. Taku Glacier experiences low strain rates compared with other Alaskan tidewater glaciers (Pfeffer and others, 2000; O'Neel and others, 2003; Truffer and others, 2009), resulting in less crevassing which allows us to perform seismic reflection surveys on its surface.…”
Section: Field Setting and Datamentioning
confidence: 99%
“…The Taku subglacial-proglacial drainage network follows classic temperate glacier seasonal behavior (Hooke and others, 1985;Hodson and Ferguson, 1999;Riihimaki and others, 2005;Swift and others, 2005;Perolo and others, 2019), albeit with more winter activity consistant with the wet maritime climate. Our study shows that all of these processes would be capable of continuing for decades in a stable climate, able to keep Taku Glacier in its extended tidewater glacier position, if not for the fact that strong climate forcing has caused Taku Glacier to start a new retreat in 2015 CE (McNeil and others, 2020). Taku Glacier is now transitioning from the advancing phase of the tidewater glacier cycle to the retreat phase.…”
Section: Discussionmentioning
confidence: 77%
“…Climate warming has already had a significant impact on Taku Glacier, as evidenced by its mass balance record. Taku Glacier's mass balance was positive through 1989; near zero from 1989 to 2013; and has been consistently negative since 2013, thinning by 6.3 m glacierwide and losing 0.8 km 2 in area between 2013 and 2018 (McNeil and others, 2020). Retreat of ~20 m between June 2015 and June 2019 in the lower study area (newly ice-free and vegetated land was observed during a recreational site visit) indicates a long-term retreat may have started.…”
Section: Discussionmentioning
confidence: 98%